Efecto del bambú laminado como refuerzo de vigas laminadas de Pino Radiata - Chacón-Ramírez, Danny (Instituto Tecnológico de Costa Rica, 2012)
This study deals with the analysis of the effect of Guadua bamboo laminate use as reinforcement in laminated beams of Radiata Pine when they are subjected to loads perpendicular to the axis in order to compare the results obtained with beams made of Radiata pine without reinforcement. For this was studied the mechanical behavior of 10 reinforced beams and 10 beams without reinforcement. The reinforced beams were made of Radiata pine and bamboo Guadua reinforcemetne. The reinforcement was placed in the bottom of the beams. A exploratory analysis of the physical - mechanical properties of Guadua bamboo was conducted. The bamboo samples were taken of the same stock of bamboo used as reinforcement of the beams. As a result of this research was obtained a experimental capacity in bending for beams reinforced with bamboo of 569.21 kg-m. For non-reinforced beams was obtained a experimental capacity of 563.39 kg-m. These results showed that the reinforced provided by Guadua bamboo sheeting capacity increased.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Vigas laminadas; Vigas de maderas; Refuerzo; Flexión; Esfuerzo y tensión